Is it time to move away from short-acting beta-agonists in asthma management?. Issue 4 (4th April 2019) - Martin, Matthew J.; Harrison, Tim W.
Asthma is a common chronic inflammatory disease of the airways, which continues to cause considerable morbidity and unnecessary mortality across the world [1, 2]. The recognition that even mild asthma is associated with airway inflammation led to the early and widespread use of inhaled corticosteroids (ICS) from the 1970s onwards [3, 4], transforming asthma care by significantly reducing severe exacerbations and asthma deaths. However, the persistently high levels of poor asthma control and ongoing asthma deaths in the 21st century are a growing concern [5, 6] and we believe the widespread use and overuse of short-acting beta-agonist (SABA) inhalers are a major part of the problem. Frequent SABA use is associated with adverse asthma outcomes and evidence suggests replacing SABA with fast-acting LABA/ICS as reliever therapy reduces asthma exacerbation risk. We believe the time has come to move away from SABAs in asthma management. http://ow.ly/87UJ30nVGNc